Review of Asset Management Practice in Indonesian State-Owned Enterprise - Rahadi, Raden Aswin; Indrayana, Gun Gun; Afgani, Kurnia Fajar; Darmansyah, Asep; Anggoro, Yudo; Halim, Robbyson; Fitrianda, Saldy; Purbayati, Radia; Astari, Airen Widhia; Ayudiatri, Safira (Journal Integration of Management Studies, 2024)
This study examines Indonesian State-Owned Enterprises (SOEs) asset management methods, problems, and financial and operational performance effects. The report synthesizes case studies and academic research on how large organizations manage their huge and diverse asset portfolios and how governance, regulatory frameworks, and human resource practices affect their effectiveness. The research begins with case studies of talent management innovations from big Indonesian SOEs. These cases show how proactive human resource approaches can boost company commitment and reduce turnover, improving asset management efficiency. According to the research, governance and legal frameworks influence asset management techniques. Studies show that corporate governance quality affects SOE operational performance. The paper explores how reforms and legislation affect state asset management, highlighting the major changes in SOE governance and legal frameworks, particularly after economic and political reforms. Asset management difficulties for Indonesian SOEs include managing large and diverse asset portfolios, integrating modern management frameworks, and optimizing state asset revenue. According to the study, comprehensive asset management systems, governance transparency, and professional management can address these difficulties. The research examines how asset management strategies affect Indonesian SOE profitability, corporate governance, and performance measures. Strategic asset management boosts financial performance, especially profitability. SOE profitability is greatly affected by current asset and liability management. The study offers advice to Indonesian SOEs and policymakers. Enhancing financial and operational performance requires comprehensive asset management, governance changes, and strategic innovation. These efforts boost Indonesia's economy, demonstrating the importance of asset management in SOE performance.